Use Of Google Form As An Arabic Language Learning Evaluation Tool - Safitri, Fezi; Shalihah, Siti; Uyuni, Yuyun Rohmatul; Binti Haji Awang Othman, Norain (UIN ANTASARI, 2024)
The use of technology in the world of education is growing rapidly, one of which is the use of Google Forms as a learning evaluation tool. This research aims to find out how to create Google Forms as an evaluation tool in Arabic language learning. The method used in this research is library research with steps to find sources of information from various books, journals, and so on. The research results explain that Google Forms can be used to create various types of questions, including multiple choice, short answers and essays. In addition, the automation features in Google Forms enable fast and accurate proofreading, as well as systematic data storage. Thus, Google Forms has proven to be effective as an Arabic language learning evaluation tool, providing fast feedback and increasing student involvement in the evaluation process.